MO915DIETARY ADVICE IN HEMODIALYSIS PATIENTS: IMPACT OF A TELEHEALTH APPROACH DURING THE COVID-19 PANDEMIC. (29th May 2021) - Valente, Ana; Jesus, Joana; Dinis, Ana; Correia, Andre; Breda, Joana; Godinho, Joana; Oliveira, Telma; Garagarza, Cristina
Abstract: Background and Aims: Telehealth technologies are being implemented widely and can be used to provide education and self-management support to help and sustain lifestyle changes, namely in patients with chronic diseases. The purpose of this study was to assess the effect of a telehealth-delivered nutritional intervention, via the telephone, in maintenance hemodialysis (HD) patients during the coronavirus outbreak. Method: This was a multicenter observational prospective longitudinal study of a cohort of 156 patients in maintenance HD from 15 dialysis units conducted during the COVID-19 pandemic. We assigned patients to receive dietary counselling, through a phone call, according to their biochemical and nutritional parameters (potassium >5.5mEq/L; phosphorus >5.5mg/dL or <3.5mg/dL; interdialytic weight gain percentage (%IDWG) >4.5%). Dry weight, %IDWG, body mass index, potassium, phosphorus, calcium, calcium/phosphorus product, normalized protein catabolic rate, albumin and hemoglobin were recorded at baseline and 1 month after the nutrition counselling. A p-value < 0.05 was considered statistical significant. Results: The prevalence of patients with hyperkaliemia and hyperphosphatemia decreased significantly after the dietary advice (50% vs. 34.6% and 36.5% vs. 19.2%, respectively). A statistical significant reduction in serum potassium (mEq/L) [median: 6.2 (IQ:6.0-6.5) vs. 5.7 (IQR:5.3-6.1)] and phosphorus (mg/dL) [median: 6.5 (IQR: 6.1-7.2) vs. 5.5 (4.7-6.1)] was observed in patients receiving counselling for hyperkalemia and hyperphosphatemia. In addition, there was a statistical significant decrease in the prevalence of patients with hypophosphatemia (28.8% vs. 18.6%). There was also a significant decrease in the %IDWG [(median: 4.8% (IQR: 4.2-6.8) vs. 4.4% (IQR: 3.8-6.2)], although no statistically significant differences were observed in the prevalence of patients with high %IDWG. Regarding the person contacted by telephone, data showed statistically significant differences in potassium (mEq/L) [patient – median: 6.2 (IQR:6.1-6.4) vs. 5.7 (IQR: 5.4-6.0); caregiver – mean: 6.3 ± 0.3 vs. 5.7 ± 0.7] and phosphorus (mg/dL) [patient –median: 6.5 (6.1-7.2) vs. 5.6 (4.9-6.1); caregiver – mean: 6.7±0.8 vs. 5.1±1.5] values when the contact was with the patient or the caregiver. In relation to hypophosphatemia (mg/dL) (mean: 2.4±0.7 vs. 3.0±0.9) and %IDWG [median: 4.6% (IQR: 4.1-7.1) vs. 4.1% (IQR: 3.5-6.6)], the main statistically significant differences were only observed when the contact was done directly with the patient. No differences were seen whenever the contact was with the nursing homes. Conclusion: Our results suggest that telehealth-delivered dietary interventions can improve clinical and nutritional parameters in HD patients. Therefore, it may be an effective strategy to promote a continuous nutritional monitoring in these patients, at least, when or where the face-to-face option is a critical factor.